QUALITY OF LIFE OF MOTHERS OF CHILDREN WITH CONGENITAL SYNDROME AFFECTED BY ZIKA VIRUS - Costa,Paulo Rogério Lobão de Araújo (2021)
ABSTRACT Objective: To investigate how mothers of children with congenital syndrome (microcephaly) associated with Zika virus perceive their quality of life. Methods: This is a qualitative study carried out in two stages: at the Maternal and Child University Hospital and at Casa de Apoio Ninar through semi-structured interviews with mothers of children with congenital syndrome associated with Zika virus. Ten women comprised the sample. Results: In line with the critical discourse analysis, four categories emerged based on Fairclough’s 2008 assumptions: Quality of Life and Health - quality of life perception associated with the broad meaning of the term health; Quality of Life and Health Care Systems - characterized by care instability and fragmentation; Quality of Life and Free Time - lack of free time for activities of daily living and leisure; Quality of Life and Future Perspectives - lack of future perspective, considering that most participants had to stop working and studying to take care of their children. Conclusions: Mothers of children with congenital syndrome associated with Zika virus are devoted to their children’s care. Their lack of prospects was considered a consequence of the lack of time for activities of daily living and leisure.